PELATIHAN KONSERVASI AIR TANAH PADA KAWASAN TERBANGUN DI DAS WANGGU KOTA KENDARI SEBAGAI UPAYA PENCEGAHAN BANJIR - La Ode Alwi; Abdul Gafaruddin; La Gandri; Lies Indriyani; Sahindomi Bana; Vivi Fitriani (Universitas Halu Oleo, 2022)
Kendari City is part of the Wanggu watershed, which is one of the cities that still has problems related to waterlogging and flooding. Based on historical data in the last 10 years, Kendari City is an area that floods occurs almost every year. Therefore, to deal with problems in the Wanggu watershed, especially in Kendari City, it is necessary to apply water conservation technology by applying biopore infiltration holes. The purpose of this community dedication is to conduct water conservation education for flood prevention to youth groups and the community through environmental care Action. The method used in groundwater conservation activities is a participatory approach through a pilot unit involving the youth group and the local community. This activity has succeeded in making biopori infiltration holes which are applied to places that are flooded when it rains. The making and installation of biopore infiltration holes was carried out to 15 points of standing water as a pilot. the performance of the installed biopori goes well and functions as it should. This process has been monitored at the stage of monitoring and evaluation activities during the process and after the implementation of the activities.